MINDFULNESS, FAMILY RESILIENCE, AND PARENTING STRESS IN PARENTS WITH ELEMENTARY SCHOOL-AGE CHILDREN DURING THE COVID-19 PANDEMIC - Nabila, Tazkiya; Sholihah, Khofifah Umi; Al Karim, Chamilul Hikam; Kaloeti, Dian Veronika Sakti (Jurnal Psikologi, 2022)
The Covid-19 pandemic has impacts on life, especially for parents of school-age children. One of the phenomena that occur is parenting stress, which impacts parenting. Parenting stress requires the role of mindfulness and family resilience in order to be able to deal with stressful conditions of parenting during a pandemic. This study aimed to determine the relationship between mindfulness, family resilience, and parenting stress of parents who had school-age children. This quantitative study used a purposive sampling technique involving 60 parents with children of primary school age (93.3% female, Mage = 38; SD = 7.4). The instruments used in this research were the Mindful Attention Awareness Scale (MAAS) with (α = .911), Family Resilience Assessment Scale (α = .964), and The Parenting Stress Index (α = .994). The method of data analysis was multiple linear regression analysis. The result shows that mindfulness and family resilience are simultaneously statistically significant in predicting parenting stress, Adj R 2 = .936, F(2, 58) = 428.89, p < .001. In addition, it found that mindfulness does not contribute to the model, b = -.025; t(58) = -.686, p = .495, while family resilience does, b = .957; t(58) = 26.158, p < .001. The effective contribution of mindfulness and family resilience to parenting stress is 93.6%. Based on the research results obtained, parents can develop mindfulness and family resilience to cope with the perceived stress of parenting.